Canales de ventas por internet de las compañías en Colombia : establecimientos de prendas para vestir (2015)
The project presented below serves to know the impact and use of online sales channels in the establishments of garments to dress in Colombia. In addition, this investigation relies on the theory of the five competitive forces of Michael Porter where it will give the opportunity to readers to approach to two international companies in the city of Santiago de Cali, in order to evaluate the growth of the brand through the use and implementation of the virtual channel. To carry out this project, it has been made a descriptive research that allows to know the attitudes and preferences of consumers in a real environment, which subsequently took place an analysis that led to e stablish how this distribution strategy that addsa value to the brand is perceived. Finally, this research plan will offer the possibility to serve as a source of information for future projects that contribute to the study of the same kind